Illuminating the Concept of Community (Group)-Level Procedural Justice: A Qualitative Analysis of Protestors' Group-Level Experiences With the Police. (June 2021) - Jonathan-Zamir, Tal; Perry, Gali; Weisburd, David
"Procedural justice" (PJ) has traditionally been thought of as an intragroup model, characterizing interpersonal interactions between police officers and specific individuals. O'Brien et al. recently proposed that PJ is also a useful framework for examining intergroup dynamics, and can thus be used to typify interactions between the police and communities/social groups as a whole. Yet, as a novel construct, its precise content remains unclear. We use qualitative, in-depth interviews with individuals who encountered police as a group of protestors, to illuminate the constituent elements of group-level PJ. We identify four concerns with group-level treatment: respect for the existence and cause of the group, partnership with the group, recognizing the individual within the group, and displaying the "right" motivation: allowing group activities to take place safely. We discuss the implications of our findings, arguing that they pave the way for more exhaustive modeling of the fairness embedded in authorities' treatment.